A Three-Dimensional Range Migration Algorithm for Downward-Looking 3D-SAR with Single-Transmitting and Multiple-Receiving Linear Array Antennas. (22nd March 2010) - Du Du, Lei Lei; Wang Wang, Yanping Yanping; Hong Hong, Wen Wen; Tan Tan, Weixian Weixian; Wu Wu, Yirong Yirong
Abstract : This paper presents a three-dimensional (3D) range migration algorithm (RMA) suitable for downward-looking 3D-SAR with single-transmitting and multiple-receiving linear array antennas (STMR-LAA). As the round-trip range equation in 3D-SAR with STMR-LAA is a dual square root, the signal spectrum in 3D wavenumber domain contains nonlinear phase terms besides constant and linear phase terms. In this paper, the approximate expression of the signal spectrum is derived by expanding the implicit phase term to its Taylor series. Then the constant and nonlinear phase terms are calculated and compensated by multiplying the wavenumber filters. Finally, a 3D wavenumber mapping is proposed to make the signal evenly sampled in 3D wavenumber domain. Some simulating results are presented to validate the correctness of the analysis and the feasibility of the algorithm. In addition, the required accuracy on the platform position is analyzed at the end of the paper.